IMPLEMENTASI PENDIDIKAN MULTIKULTURAL DALAM PEMBELAJARAN IPA DI SMP NEGERI 7 MUARO JAMBI - Dara Mutiara Aswan; Ajeng Pramesti Cahyani; Sarah Amelia Sarah Amelia; Santo V. Simatupang (PROMOSI (Jurnal Pendidikan Ekonomi), 2022)
In Indonesia, which is an archipelagic country with unique diversity on each island, conflictsoften occur between one another. In the school, there are some conflicts between students whodo not understand multiculturalism. Therefore, this research has been done at SMP Negeri 7Muaro Jambi in Jambi Province to know the understanding of students about multiculturalism.This research is qualitative research by observing and distributing Google Forms. The results ofthis study indicate that some students have understood and practiced multiculturalism in schoolwhile others still need to be given further guidance.Keywords : Implementasi, Multikultural, Budaya